2006
DOI: 10.1074/jbc.m602144200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism Underlying Inverse Agonist of Angiotensin II Type 1 Receptor

Abstract: To delineate the molecular mechanism underlying the inverse agonist activity of olmesartan, a potent angiotensin II type 1 (AT 1 ) receptor antagonist, we performed binding affinity studies and an inositol phosphate production assay. 257 was found to be important for the interaction with olmesartan but not for the inverse agonist activity. Based on these results, we constructed a model for the interaction between olmesartan and the AT 1 receptor. Although the activation of G protein-coupled receptors is initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(140 citation statements)
references
References 27 publications
7
126
1
6
Order By: Relevance
“…9 We also found that basal c-fos promoter activity was suppressed by olmesartan in HEK293 cells expressing AT 1 -N111G (Figure 2). The inhibitory effect of olmesartan on basal c-fos promoter activity was significantly stronger than that of losartan ( Figure 3).…”
Section: Inhibitory Effects Of Olmesartan and Its Derivative Compoundmentioning
confidence: 66%
See 4 more Smart Citations
“…9 We also found that basal c-fos promoter activity was suppressed by olmesartan in HEK293 cells expressing AT 1 -N111G (Figure 2). The inhibitory effect of olmesartan on basal c-fos promoter activity was significantly stronger than that of losartan ( Figure 3).…”
Section: Inhibitory Effects Of Olmesartan and Its Derivative Compoundmentioning
confidence: 66%
“…9 The tetrazole group of olmesartan also interacts with Gln 257 of the AT 1 receptor, but its binding is not required to reduce the basal activity level of the AT 1 receptor. 9 We first examined the effect of olmesartan on stretch-induced ERK activation in HEK293 cells overexpressing AT 1 -WT or an AT 1 mutant receptor harboring one of the following mutations: Y113F, K199Q, H256A or Q257A. As shown in Figure 6a, mechanical stretch-induced phosphorylation of ERKs occurred in AT 1 -Y113F, AT 1 -K199Q, AT 1 -H256A and AT 1 -Q257A cells in degrees equivalent to AT 1 -WT cells.…”
Section: Inverse Agonist Activity Of Olmesartan Y Qin Et Almentioning
confidence: 99%
See 3 more Smart Citations